(untitled) (Global Journal of Science Frontier Research, 2020)
Today, traditional media is still a significant part of disseminating weather and climate information, still they have not been able to reach out to all users of the target audience alone. On the other hand, social media platforms such as Twitter, Facebook, YouTube, Instagram, etc. are used as a tool of communicating weather and climate information to various users in a wellorganized manner like never before. Using a scientific research methodology of case study, the research was designed to explore how the Kenya Meteorological Department (KMD) is using Twitter and Facebook accounts for weather and climate information dissemination to various users.